PERAN TAMAN VATULEMO DALAM MITIGASI BENCANA STUDI AKSESIBILITAS MENGGUNAKAN RADIUS BUFFER - Nike Dyah Permata; Dui Buana Mustakima; Cahyani; Nurul Hikmah; Isti Nugroho1 (Archvisual: Jurnal Arsitektur dan Perencanaan, 2025)
Vatulemo Park is a public open space that is quite popular with the people of Palu City. Vatulemo Park has the role of a park and is one of the images of Palu City. In addition, city parks can also function as city infrastructure in disaster mitigation. This study aims to analyse the level of role of Vatulemo Park as a public open space and as a space for evacuation, as well as disaster mitigation. In 2018, Palu City was hit by earthquakes, tsunamis, and liquefaction. Therefore, it is necessary to have a public open space that can be accessed by the public as an evacuation space and gathering point when a disaster occurs to increase community resilience to disasters. The method used in this study is to use a radius buffer approach based on Geographic Information System (GIS). The study was carried out by mapping the location of Vatulemo Park and measuring its coverage to the surrounding population based on the ideal mileage (500 – 1,000 cashews or 5-10 minutes walk and vehicle) from densely populated settlements. The results of the analysis show that Vatulemo Park is accessible to about 8,160 people, making it a strategic location for disaster mitigation. City parks can minimise panic and casualties in the event of a disaster. Therefore, accessibility for vulnerable groups needs to be improved, such as supporting facilities in the form of evacuation signs and lighting installations, and programs to educate when disasters occur, such as disaster simulations. Based on the results of research, Vatulemo Park has the potential to be one of the evacuation rooms and gathering points when disasters occur. Vatulemo Park is in the middle of a densely populated settlement, so it will make it easier for the community to go to the evacuation location or gathering point. Improved accessibility, infrastructure, and community preparedness will optimise the park's role as an important element in the development of disaster-resilient cities.